1997
DOI: 10.1046/j.1365-3083.1997.d01-386.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrary Roles of IL‐4 and IL‐12 on IL‐10 Production and Proliferation of Human Tumour Reactive T Cells

Abstract: The cytokine profile of tumour reactive T cells is likely to play a central role in their function. However, little is known about how cytokine patterns of tumour reactive T cells can be regulated. Here, the authors investigated the influence of exogenous regulatory cytokines in addition to interleukin-2 (IL-2) on cytokine patterns and the proliferation of T cells recognizing an autologous sarcoma cell line. In this system, IL-4 and IL-12 showed the most polarizing influences on tumour reactive T cells. Exogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The striking difference in IFN-γ and IL-2 gene expressions indicates that these cytokines are under separate control. Moreover, IL-12 is a potent stimulus for IFN-γ secretion by NK cells [48, 49]. IFN-γ then stimulates macrophage activation which among numerous responses includes increased cytokine synthesis, ultimately leading to even more NK cell IFN-γ production [50].…”
Section: Discussionmentioning
confidence: 99%
“…The striking difference in IFN-γ and IL-2 gene expressions indicates that these cytokines are under separate control. Moreover, IL-12 is a potent stimulus for IFN-γ secretion by NK cells [48, 49]. IFN-γ then stimulates macrophage activation which among numerous responses includes increased cytokine synthesis, ultimately leading to even more NK cell IFN-γ production [50].…”
Section: Discussionmentioning
confidence: 99%
“…IL-4 can inhibit a variety of IFN-γ functions (Heike et al 1997;Tipping et al 1997) as well as the synthesis of proinflammatory cytokines such as IL-1β, TNF-α, and IL-6 by monocytes/macrophages (Essner et al 1989;Hart et al 1989;Te Velde et al 1990). Considering that the inflammation shifted to the chronic phase in the late experimental period, Th2 may regulate inflammatory events, including bone resorption, in the late phase of this model, but not in the early phase.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging experimental evidences indicate that HLA-DR antigens expressed on neoplastic cells can play an important role in tumor immunology, and that alterations in their levels of expression might affect tumor immune escape (Heike et al, 1996;Byrne and Halliday, 2003). Based on this idea, different studies have focused on the prognostic value of HLA-DR antigens expression on solid malignancies; however, the results obtained so far are still contradictory.…”
Section: Distribution Of Hla-dr Antigens In Solid Malignanciesmentioning
confidence: 99%
“…In this regard, experimental findings have shown that selected tumor-associated antigens (TAA) are effectively presented by HLA class II antigens to CD4 þ T cells (Renkvist et al, 2001;Tatsumi et al, 2003). Furthermore, it has been demonstrated that solid tumor cells can themselves act as nonprofessional APC being directly able to stimulate the proliferation of autologous CD4 þ T cells (Heike et al, 1996). However, it has also been suggested that tumor cells drive T cells in an anergy state that results in immunosuppression of tumor-reactive T-cell clones (Byrne and Halliday, 2003).…”
Section: Introductionmentioning
confidence: 99%